Integrated method of non-thermal plasma combined with catalytical oxidation for simultaneous removal of SO2 and NO. (15th June 2019) - Cui, Shaoping; Hao, Runlong; Fu, Dong
Highlights: A MnCe/Ti catalyst with good oxidation performance for NO and SO2 was prepared. A NTP catalytic oxidation system was constructed to simultaneously remove NO and SO2 . Highest NO and SO2 removal efficiencies (86.9% and 100%) were achieved. Removal efficiency and interactions between NO and SO2 were analyzed. The novel reactor enhanced the removal efficiency and reduced the energy consumption. Abstract: In this paper, non-thermal plasma (NTP) discharge and catalyst were integrated, and the dielectric barrier discharge (DBD) reactor was used to prepare a MnCe/Ti catalyst. We then measured its surface characteristics. A NTP catalytic oxidation experimental system based on the MnCe/Ti catalyst was constructed for simultaneous desulfurization and denitrification, and the efficiency of the system for the simultaneous removal of NO and SO2 in simulated flue gas was verified. The effects of specific energy density (SED), flue gas flow rate, and the initial concentrations of NO and SO2 on the removal efficiencies as well as the interactions between NO and SO2 were analyzed. The NO and SO2 removal efficiencies and the corresponding energy efficiency of the integrated system were compared to the system using only the DBD reactor. The results showed that the MnCe/Ti catalyst exhibited higher dispersion of metal oxide active components on the surface and had a higher content of catalytic oxidation active substances than non-doped Mn/Ti and Ce/Ti catalysts. With a SED in the range of 30–250 J/L, the NO and SO2 removal efficiencies increased as the SED increased. At low initial concentrations (200 mg/m 3 NO and 1000 mg/m 3 SO2 ), the highest NO and SO2 removal efficiencies (86.9% and 100%) were achieved. Versus the flue gas treatment system using only the DBD reactor, the system using the MnCe/Ti catalyst-filled DBD reactor simultaneously removed NO and SO2 with enhanced efficiencies and reduced system energy consumption—this is a reference for further optimization of the flue gas treatment system using a DBD-wet electrostatic precipitator (WESP).